2022
DOI: 10.1007/s13198-022-01765-4
|View full text |Cite
|
Sign up to set email alerts
|

Predicting child anaemia in the North-Eastern states of India: a machine learning approach

Abstract: Child anaemia is a serious global health issue and India is one of the highest contributors among the developing nations. Researchers identify many harmful effects of anaemia, which include psychomotor retardation, which in turn decreases the learning ability and causes low intelligence among pre-school children. The effects also include behavioural delays, low immunity, and susceptibility to frequent infections, increased mortality, and disability. The present study aims to predict anaemia among children in N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…The logistic regression model revealed that a child aged between 6 and 23 months, mother’s age < 20 years old, mother’s anaemia, child stunting, and wasting are the most important predictors of childhood anaemia. This finding is consistent with a study from India [ 24 ]. Child nutrition, mother’s age, unemployed mother, no drug for parasites within the previous 6 months, and child morbidity are important predictors identified by both logistic regression and RF consistently, even though their degree of importance varies.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The logistic regression model revealed that a child aged between 6 and 23 months, mother’s age < 20 years old, mother’s anaemia, child stunting, and wasting are the most important predictors of childhood anaemia. This finding is consistent with a study from India [ 24 ]. Child nutrition, mother’s age, unemployed mother, no drug for parasites within the previous 6 months, and child morbidity are important predictors identified by both logistic regression and RF consistently, even though their degree of importance varies.…”
Section: Discussionsupporting
confidence: 94%
“…The diagnosis of childhood anaemia is resource intensive and challenging particularly in rural settings where there is scarcity of resources [ 21 ]. Previous studies show improved ML performance in predicting childhood anaemia [ 23 , 24 ]. Therefore, the aim of this study is to apply a machine learning (ML) algorithm to predict childhood anaemia using the already established risk factors for childhood anaemia.…”
Section: Introductionmentioning
confidence: 99%